IMPROVING THE MANAGEMENT ACTIVITIES OF EDUCATIONAL INSTITUTION LEADERS BASED ON INTERNATIONAL REQUIREMENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article presents information on improving the management activities of leaders of educational institutions based on international requirements and analyzing the achieved outcomes. The effectiveness of leaders’ managerial activities is discussed, with particular attention given to foreign experience, international standards, and the organizational and managerial practices required for achieving high performance in educational institutions. The study provides explanations of managerial approaches that enable leaders to ensure effective governance and sustainable development within educational organizations.